Randomized controlled trial evaluating the utility of urine HPV DNA for cervical cancer screening in a Pacific Island population. (2018) - Hernandez, Brenda Y.; Tareg, Aileen C; Reichhardt, Martina; Agapito, Angelica; Zhu, Xuemei; Sy, Angela; Yuji, Arnice; Killeen, Jeffrey; Chan, Owen; Buenconsejo-Lum, Lee E
No abstract available